(untitled) - Nishida, Kitaro (Tokyo, 1958)
The essays which comprise these companion volume have been selected from the proceedings of the East-West Philosopher's conferences held during the past 15 years. Here are examinations by world authorities of the rich, varied, and complicated philosophies of these countries.
Keywords: Philosophy, japanese,Philosophy